INFORMATION AND COMMUNICATION TECHNOLOGIES IN PEDAGOGICAL ACTIVITIES - Lúcia Nunes Gomes da Costa, Alba; Maria Tavares Gomes, Cláudia (Revista Gênero e Interdisciplinaridade, 2023)
In view of the use of technology in education can be an important resource in the cognitive development of student. This study arose from the need of encourage the use of information and communication technologies within school environment, in how classes are planning, political pedagogical projects and to insert the informatics in the continuing education of teachers. Some authors had contributed to this study, such as Tardiff (2014), Moran, Masetto e Behrens (2006), Grisnpun et al (2002), Freire (2001), Almeida (2009), Vigneron e Oliveira (2005), Lévy (2011/2014), Gadotti (2011), among others. The data were collected from the participatory and qualitative research, which made clear the need to implement a course focused on the use of information and communication technologies into the education of teachers. The study enabled more effective educational practices, knowledge mediation and acquisition of technological skills by teachers, through the course Introduction to Digital Education. It also shows that the difficulty of teachers in dealing with technology in the classroom, goes beyond the skills acquired in the teaching profession, including factors such as space, physical structure of the school and continuing education on the use of technology in education